Sexual variation in two species of Helorus Latreille (Hymenoptera, Heloridae) from NW China, with description of female of Helorus caii He & Xu - Zhang, Ruo-Nan; Achterberg, Cornelis Van; Tian, Xiao-Xia; He, Cheng-Yi; Tan, Jiang-Li (Zootaxa, 2020)
The intra-specific variation of two species of Helorus Latreille (Hymenoptera, Heloridae) from NW China is studied and for the first time the sexual variation in Chinese Helorus species is described. Both sexes of Helorus antefurcalis He & Xu, 2015 (new for Shaanxi) and H. caii He & Xu, 2015 (up to now only known from one male), are described and illustrated. Helorus xinjiangensis He & Xu, [June] 2015, is a new junior synonym of H. alborzicus Izadizadeh, van Achterberg & Talebi, [April] 2015 and H. elgoni Risbec, 1950, is re-instated as valid species. A revised key to the Old World species of Helorus Latreille (except Australian region) is included.